Modeling specific antibody responses to natural immunization to predict a correlate of protection against infection before commencing a clinical vaccine trial - Anthony Almudevar; Michael E. Pichichero (Taylor & Francis Group, 2017)
Background Clinical trials of vaccines for children to prevent acute otitis media (AOM) infections caused by the bacteria Streptococcus pneumonia (Spn) are in Phase I. The objective of this study was to use serum antibody measurements to pneumococcal purified protein candidate antigens that occurred after natural "immunization" to predict a correlate of protection response needed following an injectable vaccine against AOM in children. Methods 590 nasal and serum samples were collected from 129 healthy children at 6, 9, 12, 15, 18, 24 and 30-36 months of age and when the child developed AOM. Middle ear fluid to detect Spn was collected at every episode of AOM. Quantitative ELISA was used to determine serum IgG against 7 Spn vaccine antigens: PspA clade 3, PspA clade 5, PhtD, PhtE, LytB, PcpA and Ply. A correlate of protection (COP) was estimated by regressing AOM events against age adjusted antibody levels induced by nasopharyngeal colonization and AOM infections, using logistic regression and generalized estimating equation methods. Results A significant COP was found for Spn PhtD (p = 0.0015), PhtE (p = 0.00034), LytB (p = 0.004), PcpA (p = 0.002), and Ply (p = 0.007) between higher antibody levels and reduced frequency of AOM. We estimated that a 2-fold higher antibody level in a child than the mean antibody level induced by NP colonization (after adjusting for subject age) to PhtD, LytB, PcpA, PhtE or Ply reduced the risk of AOM by 14-21%, a 4-fold higher level reduced it by 25-38% and a 10-fold higher level reduced it by 39-54%. Conclusion We developed a model to predict the necessary level of serum antibody and fold higher above a threshold to PhtD, PhtE, LytB, PcpA and Ply that would correlate with a reduced likelihood of AOM in children age 6-24 months old if enrolled in a Phase III clinical efficacy trial.